Body Mass Index Impact and Predictability on Preeclamptic Toxemia - Khaled M AbdAllah; Ahmed Abdelhamid; Omar Abd El Fattah Ahmed Nagy (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2018)
Background: PET is a systemic disorder of vascular endothelial dysfunction and vasospasm that occurs after 20 weeks' gestational age and can present as late as 4-6 weeks postpartum. It is clinically defined by hypertension and proteinuria, with or without pathologic edema. Maternal obesity is a prominent hazardous risk factor for the pathological development of PET.  Aim: To determine the correlation between the raised body mass index and the risk of PET.  Methods: Research study performed on 400 recruited cases attending the antenatal care unit of Al-Azhar University Hospital (Assiut) they were recruited at 20 weeks of gestation and follow up was performed at 28 and 36 weeks of gestation. They were categorized into 5 research groups (each n=80) according to the selectivity criteria of their Body Mass Index BMI (kg/m2) at 20 weeks of gestational age. Research group A (n=80): normal BMI (18.50-24.99 kg/m2) research group B (n=80): overweight BMI (25-29.99 kg/m2) Group C (n=80): obese class I BMI (30-34.99 kg/m2) research group D (n=80): obese class II BMI (35-39.99 kg/m2) Research group E (n=80): obese class III BMI (>40 kg/m2). Follow up for PET development was performed to analyze the correlation between BMI and PET development. Developed in 5 cases in the group A (6.25%), 6 cases in the group B (7.5%), 9 cases in the group C (11.2%), 13 cases in the group D (16.2%), 16 cases in the group E (20%). Among these 11 cases developed severe preeclampsia in groups B, C, D, and E. It has been evident in the present study that the incidence of preeclampsia (either mild or severe) in cases of increased BMI (groups B, C, D, and E) was 13.75%. While the incidence of preeclampsia in the general population (group A) is cited to be 6.25%. Relative risk to general population=incidence of preeclampsia in people exposed (13.75%) / incidence in general population (6.25%) =2.2.